Essential Oil Nanoemulsions and their Antimicrobial and Food Applications. - PATHANIA, RUHI; KHAN, HUMA; KAUSHIK, RAVINDER; KHAN, MOHAMMED AZHAR (Current Research in Nutrition & Food Science, 2018)
The consumer awareness for secure insignificantly handled food has constrained the food dealers either to decrease the measure of chemically synthetic antimicrobial substances or to replace them with natural ones. Essential oils (EO) extracted from edible, therapeutic and herbal plants have been well recognized as natural antimicrobial additives. As characteristic then viable antimicrobials, EO have been progressively observed towards control of foodborne microbes and progression of nourishment wellbeing. It is ordinarily hard to achieve high antimicrobial vulnerability when mixing with EO in nourishment based items because of low dissolvability of water and interactive binding. Subsequently, the delivery system of nanoemulsion-based EO is emerging as a viable solution to control the growth of foodborne pathogens. Lipophilic compounds are distributed uniformly in the aqueous phase with the help of nanoemulsion technique. Therefore, the nanoemulsion formulation is generally comprised of mainly three constituents i.e. oil phase, aqueous and a surfactant. Nanoemulsions droplet average diameters should below 100 nm. According to previous studies, the clove, cinnamon and thyme oil nanoemulsions which were formulated with non ionic surfactants (Spans and Tweens) were having droplet size less than 100nm. The current review emphases on essential oil based nanoemulsions which are prepared with different ingredients which hence, enhance the antimicrobial action in food items.